Social isolation in rats: effects on animal welfare and molecular markers for neuroplasticity - Begni, Veronica; Sanson, Alice; Pfeiffer, Natascha; Brandwein, Christiane; Inta, Dragos; Talbot, Steven R.; Riva, Marco Andrea; Gass, Peter; Mallien, Anne Stephanie (PLOS ONE, 2020)
Early life stress compromises brain development and can contribute to the development of mental illnesses. A common animal model used to study different facets of psychiatric disorders is social isolation from early life on. In rats, this isolation can induce long-lasting alterations in molecular expression and in behavior. Since social isolation models severe psychiatric symptoms, it is to be expected that it affects the overall wellbeing of the animals. As also promoted by the 3Rs principle, though, it is pivotal to decrease the burden of laboratory animals by limiting the number of subjects (reduce, replace) and by improving the animals’ wellbeing (refine). The aim of this study was therefore to test possible refinement strategies such as resocialization and mere adult social isolation. We examined whether the alternatives still triggered the necessary phenotype while minimizing the stress load on the animals. Interestingly, we did not find reduced wellbeing-associated burrowing performance in isolated rats. The hyperactive phenotype seen in socially isolated animals was observed for rats undergoing the adult-only isolation, but resocializing ameliorated the locomotor abnormality. Isolation strongly affected markers of neuroplasticity in the prefrontal cortex independent of timing: mRNA levels of Arc, Bdnf and the pool of Bdnf transcripts with the 3’ long UTR were reduced in all groups. Bdnf splice variant IV expression was reduced in lifelong-isolated animals. Some of these deficits normalized after resocialization; likewise, exon VI Bdnf mRNA levels were reduced only in animals persistently isolated. Conversely, social deprivation did not affect the expression of Gad67 and Pvb, two GABAergic markers, whereas changes occurred in the expression of dopamine d1 and d2 receptors. As adult isolation was sufficient to trigger the hyperactive phenotype and impaired neuroplasticity in the prefrontal cortex, it could be a candidate for a refinement strategy for certain research questions. To fully grade the severity of post-weaning social isolation and the alternatives, adult isolation and resocialization, a more profound and multimodal assessment approach is necessary.
Gesehen am 12.08.2024